Transition of adolescents with congenital heart disease from pediatric to adult congenital cardiac care: lessons from a retrospective cohort study - Mondal Tapas K.; Muddaluru Varun; Jaafar Ahmad; Gupta-Bhatnagar Shikha; Greville Lucas J.; Gorter Jan Willem (De Gruyter, 2020)
The transfer from pediatric to adult care is a key milestone for adolescents living with chronic health conditions. Over the past few decades, pediatric cardiac care has witnessed outstanding advancements leading to a dramatic increase in the number of children with congenital heart disease (CHD) surviving into adulthood. Successful transfer from pediatric to adult congenital cardiac care is critical because many adults with CHD require regular long-term cardiac care for optimal health outcomes.